Effect of steaming time on the linear expansion of fish crackers ('keropok') - Kyaw, Z.Y.; Yu, S.Y.; Cheow, C.S.; Dzulkifly, M.H. (Society of Chemical Industry, 1999)
The effect of steaming time on 'keropok' was studied. The morphology of the starch granules in keropok gel at different steaming times was examined using scanning electron microscopy (SEM). There was an optimum time for the steaming of keropok which gave the best linear expansion and hardest texture of steamed gel. This occurred when the starch granules were expanded to their largest sizes and before fragmentation of the granules. A steaming time of 20-30 min is sufficient to cook the keropok gel. Excessive steaming time will result in a poor-quality product as well as extra production costs.